The Existence of Islam in The Face of Homogenization in Indonesia - Ulya, Vita Fitriatul; Suyanto, Ahmad; Nugrahartanti, Tiara; Abidin, Zainal (Proceedings of International Conference on Muslim Society and Thought, 2024)
A dialogic discourse suggests that globalization has marginalized the existence of religion. Religion no longer has the opportunity to address public issues. This is evident in the reality that globalization has shifted local values, including religion, and replaced them with homogenized values. Islam, as one of the world's religions, is aware that it has entered the global stage of preaching. Revitalization is one of Islam's efforts to face the challenges of the times. This article will address how Islam, as one of the world's largest religions, maintains the existence of its teachings and responds to the impact of globalization, namely homogenization. Several Western futurologists such as John Naisbitt, a scholar like John L. Esposito, and religious ideologists like Al-Maududi contribute their thoughts to this study. Using literature analysis, the author maps out the constructs of thought and responses of the Islamic community to globalization. In this context, there are differing perspectives between two groups. On one side, there are those who view homogenization negatively, believing it could destroy the existence of religion, while others believe that homogenization is not a threat but rather a motivation for Islam to maintain its existence.